#TITLE_ALTERNATIVE# - SYAPUTRA (NIM 10205037), MARHAMNI
In principle, to calculate all of the interaction between nucleons in the nucleus is too complicated. Therefore, it will be more easily if all interaction is replaced by a certain potential, while nucleon is considered independently, do not interact each other, but under influence of the potential. Fermi gas is the first independent model of the nucleus. In this model, nucleons are considered as molecular-gas that stands alone in a certain potential. The calculation use Thomas-Fermi method which is the development of the atomic-scale structure calculations with nucleons density is the main variable. This paper describes graphically the nucleon-density of the nucleus which follows the Fermi-Dirac distribution function of nuclei radius. Influence of the temperature on the nucleon-density is also discussed in this paper.